Leadership Style, Organizational Commitment and Job Satisfaction: A Case Study on High School Principals in Tehran, Iran - Omidifar, Reza (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> Teachers’ job satisfaction and commitment depends upon the leadership style of high schools principals. This study clarifies the relationship between principals’ leadership style, organizational commitment and job satisfaction. A quantitative questionnaire using Likert-type scales was administered to 357 high school teachers and principals in Tehran, Iran. The study samples were selected through stratified sampling technique. The data was tested for reliability and results presented based on the study objectives. Pearson correlation coefficient was used to explain teacher job satisfaction and commitment by leadership style. The results revealed positive and significant relationships between leadership style, organizational commitment and job satisfaction. This study also clarifies the relations of job satisfaction and commitment, and highlights the crucial role of leadership style in teachers’ job satisfaction and commitment. Hence, the school principals should select the best leadership style according to the organizational culture and employees’ capacity. Implications of the study are discussed in relation to managers and principals, as well as to policy makers at the educational level. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->